A study of the mechanical properties of cement bonded coco excelsior board for use as a construction material - Lim, Winnifred H. (1992)
Wood-cement composite has great prospects in tropical and developing countries like ours. It is because of its weather durability, incombustibility and low cost that makes this a good alternative to other conventional types of building materials. However, the technological information available is limited. It is yet to be exploited to our fullest advantage. This study of the mechanical properties of Cement Bound Coco Excelsior Board (CBCEB) for use as a structural material in low-cost housing construction could make possible the use of our limitless agricultural waste products such as coconut palm wood. However, there are several factors that would ultimately determine its economy of use and the composite's ability to serve the purpose it was mae for. First, is the uncertainty caused by the coco wood extractives on the complete hydration of cement. Secondly, the material mixing proportions and lastly, the board's density. In order to fully determine the compatibility of coco wood with cement and the potential of producing low-cost structural panels, the following were taken into consideration: 1. The suitability of using some chemical additives on coco-wood-cement mix, among those tested were calcium chloride, aluminum sulfate and Houston-466. 2. The influence of varying material mixing proportions (e.g. wood/cement ration and water/cement ratio) 3. The effect of different board densities.
The board specimens were tested using the procedure describe by ASTM D1037-89 standards for evaluating the properties of wood-base fiber and particle panel materials. Tests performed included the following: 1) static bending test; 2) compressive strength test; 3) shearing strength test; 4) nail-head pull through test; and 5) lateral nail resistance test. The economy of producing CBCEB was determined by evaluating the strength to cost ratios of various richness of the board. Optimization design methods were also studied by coming up with: 1) linear regression graph; and , 2) simplified design formulas for its optimum use. Findings in this study revealed that a strong and cheaper cement-bonded coco excelsior board can be produced at a high density level of 12520 Kg/m3 with the combination of 40/60 wood/cement ratio. 60% water and 3% calcium chloride based on cement weight Boards made at this optimum manufacturing condition surpassed the strength required by Japanese Industrial Standards (JIS A 5404-87) for wood-wool cement board. With the data collected, this should provide valuable information into the coco wood-cement compatibility, it's strength, cost and characteristics using different manufacturing formulations.
Computer print-out (photocopy).
Thesis (M.S. Civil Engineering)--University of the Philippines Diliman.
Keywords: Coconut lumber; Building materials